Boston, February 27. 1777 : Gentlemen, at a time when degenerate Britons are with brutal rage . ([publisher not identified], 1777)
February 27, 1777 Open letter by the Committee of Correspondence of Boston regarding reasons and actions taken to prevent monopolies and oppressive prices. Discusses an Act to prevent monopoly and oppression that was passed on January 25, 1777.